2020
DOI: 10.1002/jso.26166
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation cascade in postmastectomy breast reconstruction and its associated factors: Results from a long‐term population‐based study

Abstract: Background: Unplanned surgeries following postmastectomy breast reconstruction (PMBR) may be required to treat complications or to revise the reconstructed breast. The primary objective of this study was to examine factors that influenced unplanned reoperations after PMBR. Methods: A retrospective cohort study using provincial databases in Ontario, Canada, was completed. Patients with breast cancer underwent mastectomy between April 2002 and March 2012 followed by immediate or delayed PMBR. Primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previous studies have generated conflicting results regarding the impact of procedure type on the need for revisional surgery 8 , but this is likely to reflect heterogeneity in the definitions of revision used and the duration of follow-up in the included studies. Two recently published large North American studies 24 , 25 have both suggested that revision rates are higher after autologous reconstruction. The first 25 included 1996 women from the Mastectomy Reconstruction Outcomes Consortium prospective cohort with 2 years’ postoperative follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have generated conflicting results regarding the impact of procedure type on the need for revisional surgery 8 , but this is likely to reflect heterogeneity in the definitions of revision used and the duration of follow-up in the included studies. Two recently published large North American studies 24 , 25 have both suggested that revision rates are higher after autologous reconstruction. The first 25 included 1996 women from the Mastectomy Reconstruction Outcomes Consortium prospective cohort with 2 years’ postoperative follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The first 25 included 1996 women from the Mastectomy Reconstruction Outcomes Consortium prospective cohort with 2 years’ postoperative follow-up. Although complications after autologous reconstruction, such as fat necrosis or wound healing problems, occur in the early postoperative phase 24 , implant-related complications including malposition or capsular contracture are more likely to occur several years after surgery. Two years would not be sufficient to capture the impact of these issues, which may explain the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 SSI results in a substantial health care burden arising from readmission, repeated surgery, and reconstructive failure, all of which can compromise quality-oflife outcomes. 4,5 The higher rates of infection after implant-based PMBR have been attributed to the presence of bacteria in the breast gland; mastectomy flap ischemia; and the placement of foreign bodies such as acellular dermal matrix (ADM), mesh, drains, and the implant or tissue expander itself.…”
Section: Ementioning
confidence: 99%